Modular cone-and-plate device for mechanofluidic assays in Transwell inserts - Chavarria, Daniel; Georges, Kissamy A.; O’Grady, Brian J.; Hassan, Khalid K.; Lippmann, Ethan S. (Frontiers in Bioengineering and Biotechnology, 2025)
In this work, we present a cost effective and open-source modular cone-and-plate (MoCAP) device that incorporates shear stress in the popular Transwell® insert system. This system acts as a lid that incorporates flow into 24-well Transwell® inserts while preserving the ability to conduct molecular profiling assays. Moreover, the MoCAP device can be rapidly reconfigured to test multiple shear stress profiles within a single device. To demonstrate the utility of the MoCAP, we conducted select assays on several different brain microvascular endothelial cell (BMEC) lines that comprise models of the blood-brain barrier (BBB), since shear stress can play an important role in BBB function. Our results characterize how shear stress modulates passive barrier function and GLUT1 expression across the different BMEC lines. Overall, we anticipate this low cost mechanofluidic device will be useful to the mechanobiology community.